Penerapan Metode CAPM (Capital Asset Pricing Model) Untuk Menentukan Pilihan Investasi pada Saham: Studi Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2022 - Rizka Dwi Silfiah; Muhammad Ilham Wardhana Haeruddin; Nurman; Amiruddin Tawe; Annisa Paramaswary Aslam (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2023)
This research aims to determine the optimal stock portfolio using the CAPM method for mining sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The population in this research is Mining Sector Companies Listed on the Indonesian Stock Exchange for the 2020-2022 Period. The samples are companies listed on the IDX for the 2020-2022 period and companies that have closing share price data for mining sector companies for the 2020-2022 period. The data collection technique used is the documentation method, while the data analysis technique uses the CAPM (Capital Asset Pricing Model) method. The research results showed that of the 30 companies that were the research sample, there were 20 companies included in the optimal portfolio, namely 20, namely PTBA, INDY, ANTM, HRUM, ADRO, ITMG, INCO, SMMT, BUMI, BSSR, BRMS, ENRG, MDKA, MYOH, DSSA, TOBA, DEA, CITA, MBAP, and IFSH. Meanwhile, there are 7 companies that are not optimal, namely GEMS, TINS, GGRP, BYAN, DOID, ZINC, and SURE